A Brief Guide to Studying Fear in Developing Rodents: Important Considerations and Common Pitfalls. Issue 1 (26th April 2018) - Cowan, Caitlin S.M.; Richardson, Rick
Abstract: Development is a time of rapid change that sets the pathway to adult functioning across all aspects of physical and mental health. Developmental studies can therefore offer insight into the unique needs of individuals at different stages of normal development as well as the etiology of various disease states. The aim of this overview is to provide an introduction to the practical implementation of developmental studies in rats and mice, with an emphasis on the study of learned fear. We first discuss how developmental factors may influence experimental outcomes for any study. This is followed by a discussion of methodological issues to consider when conducting studies of developing rodents, highlighting examples from the literature on learned fear. Throughout, we offer some recommendations to guide researchers on best practice in developmental studies. © 2018 by John Wiley & Sons, Inc.